Context-Based Routing in Dynamic Networks - Wenning, Bernd-Ludwig.; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner, 2010)
Routing in dynamically changing networks is a challenge, especially when the current context, usually consisting of multiple criteria, is used as a quality measure and decision metric. Bernd-Ludwig Wenning presents a context-based routing framework which can be applied to routing in different application domains. The routing framework includes the signaling as well as a decision system that is applied for route selection. The author chooses two application domains to evaluate the routing framework: logistic transportation networks and wireless sensor networks. He shows that this routing framework can be considered as a basis for future research in the area of context-based routing, as it opens manifold directions for further applications and enhancements.
State of the Art -- Context-based Routing Protocol Development -- Multi-Criteria Decision Systems -- Analytical Examination of Route Discovery Traffic -- Evaluation in Logistic Networks -- Evaluation inWireless Sensor Networks -- Conclusions and Outlook.
Keywords: Computer science; Computer Science; Computer Science, general